Early Onset Hypocalcaemia in Sick Newborns: A Prospective Observational Study - Sonowal, Rimjhim; Kumar, Ashok (Journal of Nepal Paediatric Society, 2022)
Introduction: Calcium physiology is in transitional state after birth and may be deranged by various neonatal disorders leading to hypocalcaemia. Coexisting hypocalcaemia can further worsen underlying condition and increase mortality. This prospective observational study was done to study the incidence, clinical correlates and outcome of early onset hypocalcaemia in sick newborns. Methods: A prospective observational study was done on 175 sick newborns. Ionized serum calcium levels were measured at six, 24, 48 and 72 hours of age by arterial blood gas analyzer. Maternal and neonatal characteristics, ionized calcium levels, clinical course and outcomes were recorded. Patient characteristics and neonatal morbidities were compared between hypercalcaemic group and normocalcaemic group by chi square test. Odds ratio was calculated to see correlation between hypocalcaemia with respiratory support and death. Results: Early onset hypocalcaemia occurred in 101 of 175 (57.7%) sick newborns. Early onset hypocalcaemia was higher in preterm babies (59.7%) than term babies (54.1%). Meconium stained amniotic fluid, obstructed labour and MAS were significantly associated with early onset hypocalcaemia. Newborns with MAS and HIE had high incidence of hypocalcaemia in both term and preterm groups. Newborns with hypocalcaemia were more likely to receive mechanical ventilation (OR 2.84; CI 1.28-6.30; p value 0.01) and had higher mortality (OR 2.10; CI 1.02-4.33; p value 0.04). Conclusions: Early onset hypocalcaemia is very common in sick newborns. Meconium aspiration syndrome was a significant risk factor for early onset hypocalcaemia. Early onset hypocalcaemia was associated with higher odds of receipt of mechanical ventilation and mortality